Pengaruh Persepsi, Motivasi, Minat dan Pengetahuan Mahasiswa Tentang Pajak terhadap Pilihan Berkarir Dibidang Perpajakan: (Studi Empiris STIE Putra Perdana Indonesia Tangerang) - Aini, Nur; Goenawan, Yohanes August (LPPM STIE PPI, 2022)
Introduction/Main Objectives: To determine the influence of students' perceptions, motivation, interests and knowledge about taxes on career choices in the field of taxation. Background Problems: Lack of student interest in the taxation sector where it is difficult to find experts in the field of taxation. Novelty: Re-examining variables that have existed in previous studies with different research locations. Research Methods: Type of quantitative research with data collection methods using the questionnaire method which is distributed online, sampling using the slovin formula with a population of 274 students and analysis tools using SPSS 25. Finding/Results: Partially variable perceptions, motivation, and student knowledge about taxes do not have a significant effect on career choices in the field of taxation and the interest variable has a significant effect on career choices in the field of taxation. Conclusion: Always deepen your knowledge of taxation by participating in a series of activities such as seminars, training or doing internships in the tax industry